Evaluation of the hydrodynamic instabilities induced by supersonic steam jet - Afrasyab, Khan (Universiti Malaysia Sarawak, (UNIMAS), 2015)
There are myriad processes involved steam-water interaction that include processes prevailed in steam driven power industries, paper and pulp industries, food preservation industries, explosive manufacturing and casting related industries and all those processes where the direct contact of heat with the material to supply could be hazardous. The present study is an effort to address the issue of investigating hydrodynamic instabilities that creates between steam and water, when supersonic steam jet is injected into the water. The effect of the hydrodynamic parameters on the hydrodynamic instability has also been investigated and then the physical consequences that are imparted by these hydrodynamic instabilities have also been investigated in terms of stresses and deformations produced by these instabilities. These instabilities have been observed for the first time with the help of the LM35 precision temperature sensors. These sensors have the high sample rate which facilitates in the fast acquisition of the temperature data. Due to the high sample rate temperature sensors it would be made possible that the transient temperature fluctuations could be acquired in the form of temperature fluctuations that depicts the strength and spatial occurrence of these instabilities. These instabilities have been observed by two methods; first with LM35 temperature sensors and then Electric Resistance Tomography (ERT) system has been used to observe the cross sectional scans of the regions inside and around steam jet with the help of variation in the electric conductivity of the surrounding fluid i.e. water. To investigate the ways to attenuate these instabilities with the varying hydrodynamic condition it has been found that the surrounding water temperature has more profound effect on the attenuation of these instabilities as compared to the inlet pressure. The effects drawn by these instabilities on the structures have been numerically calculated by using the single way coupling of the Ansys® 14.0 (Fluent) with the Ansys® 14.0 (Mechanical) to access the extent of deformation in the accompanying structures which in the current study is a Perspex vessel. It is observed that v hundreds of Pico scale deformations incurred into the Perspex vessel at the steam inlet pressure of 3.0 bars steam gauge pressure and surrounding water temperature of 600C.